2020
DOI: 10.1126/sciadv.aba6790
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall triggers more deep-seated landslides than Cascadia earthquakes in the Oregon Coast Range, USA

Abstract: The coastal Pacific Northwest USA hosts thousands of deep-seated landslides. Historic landslides have primarily been triggered by rainfall, but the region is also prone to large earthquakes on the 1100-km-long Cascadia Subduction Zone megathrust. Little is known about the number of landslides triggered by these earthquakes because the last magnitude 9 rupture occurred in 1700 CE. Here, we map 9938 deep-seated bedrock landslides in the Oregon Coast Range and use surface roughness dating to estimate that past ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…Large rockslides are major landscape modifiers in mountainous regions 1 and often induce secondary and cascading hazards, such as rockslide-induced impulse waves 2 or valley damming with subsequent outburst floods 3 . Documented rockslides are mostly triggered by heavy precipitation 4 , 5 or severe earthquakes 6 . Some prehistoric rockslides were of extraordinary size, and if similar events were to occur today they would have devastating impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Large rockslides are major landscape modifiers in mountainous regions 1 and often induce secondary and cascading hazards, such as rockslide-induced impulse waves 2 or valley damming with subsequent outburst floods 3 . Documented rockslides are mostly triggered by heavy precipitation 4 , 5 or severe earthquakes 6 . Some prehistoric rockslides were of extraordinary size, and if similar events were to occur today they would have devastating impacts.…”
Section: Introductionmentioning
confidence: 99%
“…In attempts to link OCR slope failures with known triggering mechanisms, most prior landslide dating has relied on 14 C dating of organic material collected from landslide deposits (e.g., Benda, 1990;LaHusen et al, 2020;Pierson et al, 2016;Reneau & Dietrich, 1991;Reneau et al, 1986). In addition, surface (topographic) roughness dating of landslides, where rougher (smoother) landslide deposits are younger (older), has been used to map and construct landslide age databases (Booth et al, 2009(Booth et al, , 2017LaHusen et al, 2016).…”
Section: Dating Landslide Damsmentioning
confidence: 99%
“…In addition, these new landslide ages Dams with numeric labels are those we date here and are numbered according to Table 1. Dams with alphabetic labels are dams with existing age control: A: Ayers Lake (1975 AD; Thrall et al, 1980), G: Gould Lake (1894 AD; Zybach, 2003), K: Klickitat Lake (winter 1751/52 AD; Struble et al, 2020), L: Loon Lake (∼1460 years BP; Baldwin, 1958), S: Sitkum (>3,000 years BP; LaHusen et al, 2020;Lane, 1987), T: Triangle Lake (>42000 years BP; Worona & Whitlock, 1995), W: Wasson Lake (winter 1819/20 AD; Struble et al, 2020). Black box corresponds to border of Figure 2.…”
mentioning
confidence: 99%
“…In particular, it was observed that the fault rupture mechanism strongly influences the distribution of landslides, which are usually more abundant on the hanging wall in the case of reverse or normal faults (Sato et al, 2007) and present a symmetric distribution in the case of strike-slip faulting (Xu and Xu, 2014). In the case of co-seismic landslides related to earthquakes in subduction zones, very few data and inventories are available (LaHusen et al, 2020;Schulz et al, 2012;Serey et al, 2019;Wartman et al, 2013). Best examples are the landslides induced by the 2010 Chile megathrust earthquake (Serey et al, 2019) and by the 2011 Tohoku earthquake in Japan (Wartman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate processes such as shallow landslides and debris flows are common in the case of an earthquake, but they are relatively poorly documented for past events. Debris flows, often called lahar in volcanic environments, are usually associated with eruptions that induce ice melt or snowmelt or with intense rainfalls occurring during intra-eruptive phases (e.g., Capra et al, 2018;Major et al, 2016;Manville et al, 2009). Few examples of long-runout debris flows triggered by earthquakes have been described on active volcanoes (Schuster et al, 1996;Scott et al, 2001).…”
Section: Introductionmentioning
confidence: 99%